Development of a clinical predictive model for cement loosening after vertebral augmentation in osteoporotic vertebral compression fractures - Qipeng Wei; Jinxiang Zhan; Xiaofeng Chen; Hao Li; Weijun Guo; Zihao Liu; Qingyan Huang; Dongling Cai (BMC Musculoskeletal Disorders)
Abstract Purpose This study aims to identify the risk factors associated with bone cement loosening after percutaneous vertebroplasty/kyphoplasty (PVP/PKP) for osteoporotic vertebral compression fractures (OVCF) and to develop a clinical prediction model for bone cement loosening. Methods Clinical data of patients who underwent PVP/PKP for OVCF at Guangzhou Panyu Hospital from June 2017 to June 2021 were collected, with a division into loosening group and normal group based on postoperative follow-up imaging. Univariate analysis was conducted to explore the correlation between clinical data and bone cement loosening. Multivariate logistic regression analysis was performed to identify independent risk factors for bone cement loosening after PVP/PKP for OVCF. The nomogram prediction model was constructed using R and evaluated through DCA, calibration curve, and ROC curve assessments. Results ① Multivariate analysis indicated age, time from injury to surgery, bone density, thoracolumbar kyphosis(TLK), anti-osteoporosis therapy, surgical approach, and bone cement shape were independent risk factors for bone cement loosening after PVP/PKP for OVCF. ② The nomogram clinical prediction model based on multivariate regression showed an area under the ROC curve of 0.86. The DCA curve and calibration curve demonstrated good consistency between predicted and actual results. Conclusion The clinical prediction model for bone cement loosening after PVP/PKP in OVCF indicates that advanced age, longer time from injury to surgery, low bone density, inadequate correction of thoracolumbar kyphosis, PKP, non-anti-osteoporosis therapy, and block-type bone cement are associated with a higher risk of bone cement loosening, showing excellent discriminative capacity and promising clinical utility.